Bioenergy feedstocks : breeding and genetics - Saha, Malay; Bhandari, Hem Singh; Bouton, Joseph H. (Joseph Henry), 1948- (Biomass and biofuels series., 2013)
This book looks at advances in our understanding of the genetics and breeding practices across this diverse range of crops and provides readers with a valuable tool to improve cultivars and increase energy crop yields.